Analysis of the following Related Surgeries of Unicompartmental Knee Arthroplasty and Total Knee Arthroplasty: A Taiwanese National Health Insurance Research Database Population-Based Study. (17th October 2020) - Chang, Shu-Hao; Lee, Chune-Chen; Lin, Chia-Ying; Kuo, Yu-Feng; Jiang, Ching-Chuan; Chen, Yong-Chen
Abstract : Background . Current treatment options for both unicompartmental knee arthroplasty (UKA) and total knee arthroplasty (TKA) are still controversial with no consistent results in which one is superior to others. This is the first study to examine and analyze the following related data available in patients receiving either UKA or TKA from the National Health Research Database (NHIRD) in Taiwan. Methods . The database was searched from NHIRD, pooling one million random patients. Patients' age, gender, and comorbidities were analyzed in either UKA or TKA between January 2005 and December 2013, or up until death. For the patients that had received bilateral surgeries, further subgrouping was divided into TKA to TKA, UKA to UKA, TKA to UKA, and UKA to TKA to analyze the completion rate curve. Additional analysis of the order codes 64202B, 64053B, and 64198B was defined as failures, and the related failure rate curves were analyzed separately within ten years. Finally, infection-related codes were analyzed. Results . 6, 179 patients (n = 276 UKA; n = 5903 TKA) were selected. Age (p < 0.0001 ) and gender (p = 0.037 ) had significant differences, with more young population and males having UKA than TKA. Most comorbidities had no significant difference. For the bilateral surgery analysis, the UKA to UKA group had the fastest completion rate (p < 0.001 ) and UKA to TKA was the slowest. There were no significant differences in the failure rates of 64202B, 64053B, and 64198B. Conclusion . Most UKA and TKA are appropriate solutions to treat patients with osteoarthritis or osteonecrosis. UKA to UKA is the quickest bilateral completion surgery, and UKA has a higher chance of undergoing revision surgery than TKA.